The canti-lever in the Macedonian national architecture–aspects of function, construction and materials for its aplication - Dimkov, G., Papasterevski D., Petrovski A. (DRUNPP, Sarajevo, 2015)
The usage of the cantilever expanding of masses, upper floors, from functional, particularly architectural reasons, represents an element in the Macedonian autochthon ethno architecture which is very characteristic and important, as well as the need for its complete research and examination. Throughout history, the Balkan Peninsula has constantly been a battlefield of wars and conquering. This part of Europe has been conquered by many soldiers’ legs and many civilizations have come and gone. If we remind ourselves of Greeks, Romans, Byzantium, Turkish, Serbs, Bulgarians, then, establishing this on historic facts and truths, we can claim that every civilization has left a sign during its ruling. The influence of each one is inevitable on the different aspects of life, as well as on the architecture, and also on the formation of the Macedonian national architecture and culture in general. This study will also cover the Macedonian national architecture from another angle i.e. the impact of the multinational structure of the population and the consequences of the historic immigration and migrations. Both are extremely obvious.
Keywords: cantilever, Macedonian national architecture, function, construction, constructing materials.